뒤로 걷기 운동과 언어 지시가 20대 대학생들의 앞쪽 머리 자세에 미치는 즉각적인 효과 - 박한규; Han-kyu Park; 김태호; Tae-ho Kim; 김동우; Dong-woo Kim (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2020)
Background: Backward walking exercise may offer some unique and potentially beneficial differences compared with forward walking exercise. There is still a lack of research on backward walking exercises and forward head posture. Objects: The purpose of this study was to determine the effect of backward walking exercise on college students forward head posture in their 20s. Methods: Twenty-one subjects participated in the experiment. The subjects were those with a craniovertebral angle (CVA) of 55 degrees or less who understood the purpose and method of this study and voluntarily agreed. A camera capable of taking pictures of the lateral plane was installed at a distance of 1.5 meters before exercising. Pictures were taken before walking backward, and after walking for 15 minutes on the treadmill, the images were taken in the same way. The composition of the backward walking exercise was walking at a rate of 1.0 for 5 minutes, and the remaining 10 minutes were walking at a rate of 1.5. Wilcoxon signed rank test was used to compare CVA and craniorotational angle (CRA) before and after exercise. Results: As a result of this study, there was a significant difference in CVA before and after exercise (p < 0.05). There was a significant difference in CRA before and after exercise (p < 0.05). Conclusion: The backward walking exercise and verbal command seems to have positively influenced the changes in CVA and CRA among college students in their 20s. It seems that studies to confirm balance or muscle activity as well as changes in forward head posture through the long-term intervention of the backward walking exercise should be conducted.